Self- excited oscillation under the influence of non - linear frictions - Dao, Nguyen Van (Vietnam Journal of Mechanics, 1982)
In this article the influence of friction R1, R2 on Van der Pol oscillator is considered. It turned out that the mentioned frictions decrease the amplitude of self – excited oscillations and they stabilize the equilibrium position of the self – excited system.